Associations of inflammation with symptom burden in patients with acute myeloid leukemia. (March 2018) - Lacourt, Tamara E.; Kavelaars, Annemieke; Galloway-Peña, Jessica R.; Sahasrabhojane, Pranoti V.; Shah, Nina D.; Futreal, Andrew; Kontoyiannis, Dimitrios P.; Shelburne, Samuel A.; Heijnen, Cobi J.
Highlights: Mechanisms of symptom burden in acute myeloid leukemia (AML) are poorly understood. Assessing inflammation and symptom burden before and during treatment for AML. We showed that inflammation is weakly associated with symptom burden before chemotherapy. But is strongly associated with symptom burden during chemotherapy. AML patients might benefit from anti-inflammatory interventions during treatment. Abstract: The aim of the study was to assess the association inflammation with symptom burden in patients with acute myeloid leukemia (AML), assessed before and during remission induction chemotherapy (IC). Patients with AML (n = 95) were followed from baseline (before IC) to the third week of IC for severity of self-reported somatic symptoms (assessed with the MD Anderson Symptom Inventory) and plasma levels of 13 inflammation-related biomarkers (n = 64). A composite symptom burden severity score was computed as the average score of the six most severe somatic symptoms i.e., fatigue, disturbed sleep, drowsiness, dry mouth, lack of appetite, and pain. Results from cross-sectional analyses showed that inflammation was weakly associated with symptom burden before IC (multiple regression model, explained variance = 10%) but this association grew stronger during IC (week 3 explained variance = 35%). About half of the sample showed a change over time in symptom severity. These changes were not reflected in similar changes over time in inflammatory markers, suggesting that it is the absolute concentration of a given inflammatory marker at a given time point rather than its relative change over time that is of importance. In conclusion, inflammation was strongly associated with symptom burden only during IC, possibly because expression of cytokines only then becomes relevant for regulation of symptom burden. While the current study does not allow for determination of causality, the results suggest that AML patients might benefit from anti-inflammatory interventions during treatment to alleviate somatic symptom experience.